Evaporation kinetics in swollen porous polymeric networks - Silletta, Emilia Victoria (2014)
NMR is a fast, nondestructive, and noninvasive technique that can provide information about the pore structure of macroporous polymer beads and the dynamics of liquids confined in them. In this work, we describe the study of the pore structure of the macroporous polymer of ethylene glycol dimethacrylate and 2-hydroxyethyl methacrylate [poly(EGDMA-coHEMA)] in the dry but also in the swollen state by measuring relaxation times of liquids contained in the polymer network. The results show that the pore architecture differs from the dry to the soaked state. The behavior of polar liquids during evaporation and deswelling dynamics is monitored and described. An internal migration of water from the swollen polymer mesh into expanding pores takes place. With this procedure it is possible to obtain information about the microscopic morphology behavior of the matrix during evaporation and deswelling. This information is of great interest with the aspect of possible and future applications for these types of materials.